A PRELIMINARY STUDY FOR A STRATEGIC PLANNING CONCEPT AT INVESTMENTS COMPANY - Abdalbar Mohammed Ahmed Nagasa; Mohd Syakir Mohd Rosdi (International Journal of Accounting, Finance and Business, 2024)
Despite the significant role plied by investment companies to the development of a society, the planning unit lacks experts and solely designed modules on the dimensions and elements of strategic planning in the selected study area, The situation that leads to the eclipsing stars of many investment companies in that study area, on the other hand, the absent of formidable and written strategic planning also led to the unwanted deteriorations in the major parts of the companies. This paper, taking the Al-Daman Investment Company of Libya as the focal point of this study, exhumed the weak points of the investment company of the study areas and the reasons behind that, among others. But before that, the researchers employed a qualitative interpretative methodology where context analysis was adopted, they perused many related literatures just to develop solutions to the identified menace at the end of this study. They also conducted interviews with prominent scholars in this field. The information collected was transcribed and analysed accordingly. The research yields different results, among which there are unbridle discrepancies at the implementation units in the study area, and there are many factors halting the smoothness of the investment companies in the study area. Among others. The study recommends the provision of formidable council chambers at every company well equipped with experts in the field of strategic planning, where the modules operandi on strategic planning investment should be adequately treated.